2016
DOI: 10.5492/wjccm.v5.i2.150
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of intensive care in a low resource setting: A prospective cohort of medical critically ill patients

Abstract: The ICU treatment of critically ill medical patients in a resource poor country is cost effective and compares favorably with other medical interventions. Public health authorities in low and middle income countries should encourage development of critical care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…[4] The contribution of ICU costs to total public hospital expenditure is therefore likely to be lower in SA than in countries with higher ICU bed-to-patient ratios such as the USA, with an estimated 20 -30 beds per 100 000 population. [16] The cost per ICU day (USD2 000/EUR1 815 in the trauma ICU and USD1 263/EUR1 146 in the combined ICU) in the current study is higher than the cost per day of USA193 in a medical ICU in a tertiary hospital in Sarajevo, [17] and EUR144 across 13 ICUs in Hungary. Our cost per ICU day is also higher than the USD255…”
Section: Discussionmentioning
confidence: 53%
“…[4] The contribution of ICU costs to total public hospital expenditure is therefore likely to be lower in SA than in countries with higher ICU bed-to-patient ratios such as the USA, with an estimated 20 -30 beds per 100 000 population. [16] The cost per ICU day (USD2 000/EUR1 815 in the trauma ICU and USD1 263/EUR1 146 in the combined ICU) in the current study is higher than the cost per day of USA193 in a medical ICU in a tertiary hospital in Sarajevo, [17] and EUR144 across 13 ICUs in Hungary. Our cost per ICU day is also higher than the USD255…”
Section: Discussionmentioning
confidence: 53%
“…To improve critical care service delivery in resource-limited settings, decision-makers must accept that high-quality, equitable intensive care services are necessary to achieve the Sustainable Development Goals and health security [34,106]. These services should include basic hospital resources, a reliable supply chain for essential medications and equipment [107], and a plan for human resource development [1].…”
Section: Strengthening Health Systemsmentioning
confidence: 99%
“…This results in frequent triage decisions [32], which likely increases preventable mortality [45]. Even though costs of care in ICUs of resource-limited settings are only a fraction of those encountered in HICs [46], expenses for ICU care are usually to a large extent covered by the patient's family and relatives in LMICs. Unwanted consequences can be denial or refusal of ICU admission of poor patients, but also the premature withdrawal of lifesaving interventions [47,48].…”
Section: Poor Availability Of Critical Carementioning
confidence: 99%
“…Unfortunately, there is a dearth of evidence directly from these settings to confirm this. The only economic evaluation of an ICU in Bosnia and Herzegovina concluded that critical care was highly costeffective in their setting [46]. A study from Brazil showed that the implementation of a sepsis management protocol was associated with an absolute reduction of 18% in mortality and with cost savings [55].…”
Section: Benefit Of Critical Care Among Regionsmentioning
confidence: 99%